Hand hygiene behaviours monitored by an electronic system in the intensive care unit – a prospective observational study. (May 2022) - Xu, Q.; Liu, Y.; Cepulis, D.; Jerde, A.; Sheppard, R.A.; Reichle, W.; Scott, L.; Oppy, L.; Stevenson, G.; Bishop, S.; Clifford, S.P.; Liu, P.; et al.
Summary: Background: It is difficult to improve compliance with hand hygiene (HH), and underlying behaviours are not clearly understood among healthcare workers. Aim: To study HH behaviours among healthcare workers. Methods: This was a prospective observational study. A Sanibit electronic HH system was installed in a 10-bed surgical intensive care unit (ICU) that detected HH opportunities automatically when healthcare workers entered or exited a patient room, and tracked the HH compliance of healthcare workers. The HH compliance rate and patient contact time were calculated and analysed at both ICU level and individual level over time. Findings: In total, 27, 692 HH opportunities were recorded over this 6-month trial period. The HH compliance rate was significantly higher when healthcare workers exited patient rooms than when they entered patient rooms (37.3% vs 26.1%; P <0.001). Full, partial and total HH compliance rates of 'quick in and quick out' (in room for <3 s) events were significantly lower than those of 'long in and long out' (in room for >30 s) events (23.45% vs 32.77%, 21.44% vs 35.03% and 44.88% vs 67.81%, respectively; P <0.001). There were also significant differences in HH compliance between individual healthcare workers ( P <0.001). No significant differences in overall HH compliance rate and patient contact time were found between hours of the day or days of the week, except partial HH compliance rates. Conclusion: Patterns of HH behaviours among healthcare workers are complex and variable, which could facilitate targeted and personalized interventions to improve HH compliance. Clinical Trial Registration: NCT03948672.